Using a commodity high‐definition television for collaborative structural biology. (1st June 2014) - Yennamalli, Ragothaman; Arangarasan, Raj; Bryden, Aaron; Gleicher, Michael; Phillips, George N.
<x xml:space="preserve">Abstract</x> Visualization of protein structures using stereoscopic systems is frequently needed by structural biologists working to understand a protein's structure–function relationships. Often several scientists are working as a team and need simultaneous interaction with each other and the graphics representations. Most existing molecular visualization tools support single‐user tasks, which are not suitable for a collaborative group. Expensive caves, domes or geowalls have been developed, but the availability and low cost of high‐definition televisions (HDTVs) and game controllers in the commodity entertainment market provide an economically attractive option to achieve a collaborative environment. This paper describes a low‐cost environment, using standard consumer game controllers and commercially available stereoscopic HDTV monitors with appropriate signal converters for structural biology collaborations employing existing binary distributions of commonly used software packages like Coot, PyMOL, Chimera, VMD, O, Olex2 and others.